Log(base6) - log(base 6)(x-1)=1
MY SET UP:
log_6[1/(x-1)] = 1
6^1 = 1/(x-1)
6 = 1/(x-1)
6(x-1) = 1
6x - 6 = 1
6x = 7
x = 7/6
x = 1.2
Right or wrong? If wrong, why?
1. In the original equation the argument of the first log-term is missing. According to your calculations it seems to be 1.
2. All calculations are correct - but
3. You can control your work yourself by plugging in your solution into the original equation. If you get a true statement then your work is correct.
....
121b) May I ask you a favour? Sometimes it is very difficult for me to read your questions. Why don't you use simply black colour for writing?